Elastostatic bending of a 2D-FGSW beam under nonuniform distributed loads - Chinh, Nguyen Van; Ich, Le Cong; Ngoc Anh, Le Thi; Kien, Nguyen Dinh (Vietnam Journal of Science and Technology, 2019)
Elastostatic bending behavior of a two-directional functionally graded sandwich (2D-FGSW) beam under various types of nonuniform distributed load is studied.  Based on a 3D-quasi shear deformation theory, a finite element model is derived and employed in the study. Elastostatic response of the beam is computed for the beam with different boundary conditions and aspect ratio. The effects of the material distribution and the loading type on the deflections and stresses distribution are investigated and highlighted.  The influence of the aspect ratio on the behavior of the beam is also examined and discussed